Experimental and Numerical Study on Shear Behavior of Stiffened Thin Steel Plate Shear Walls by New Welding Process - Han Xu (Infrastructures, 2022)
Steel plate shear walls (SPSW) structures have been widely employed in multistory residential buildings. The traditional welding process may lead to serious welding deformation due to the thinness of the plate. In this study, a new welding process is proposed to ensure that the stiffeners and SPSWs bend as a whole, and the number of welds is reduced from 3 to 2. This process has better integrity than the traditional process owing to less welding residual stress and deformation. On the basis of low-cycle reciprocating load tests on four full-scale specimens, the shear failure pattern, hysteresis characteristics, and load-carrying capacity of SPSWs affected by the new process are studied, and the new welding process used in the vertical stiffener can meet the requirements of shear capacity. The influences of various parameters on the shear resistance of the SPSWs made by the new welding process are compared and analyzed. The results indicate that the lateral stiffness of the frame and the width–height ratios of the wall significantly influence the load-carrying capacity of the SPSWs. The SPSWs adopting the new manufacturing process are numerically simulated using ANSYS software. The same conclusions can be obtained by comparing the numerical results with the experimental results.